2010
DOI: 10.2169/internalmedicine.49.3828
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Follicular Dendritic Cell Sarcoma Favorably Controlled by Transcatheter Arterial Chemoembolization

Abstract: A 78-year-old woman with multiple tumors in the liver and spleen was diagnosed with follicular dendritic cell (FDC) sarcoma based on the histological picture of splenectomized specimen and its expression of CD21 and CD 23. As a paraneoplastic immune disorder, Coombs' test was positive although hemolysis was not obvious. Since systemic chemotherapies were ineffective for residual liver tumors, transcatheter arterial chemoembolization (TACE) was performed with subsequent tumor reduction. Currently, the patient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In that report, the tumor showed high FDG uptake. 11 Our patient's IPT-like FDCT also showed high FDG uptake, but 18 F-FDG-PET or PET/CT may not be helpful for the differentiation of IPT-like FDCT from other splenic tumors because some splenic tumors, such as metastatic tumors or lymphomas, can also show high FDG uptake. 20 Further evaluation after the collection of many more cases is required regarding the FDG uptake of FDCTs and the utility of 18 F-FDG-PET or PET/CT for the differential diagnosis of FDCTs from other splenic lesions.…”
Section: Only 19 Cases Of Splenic Ipt-like Fdcts or Iptsmentioning
confidence: 57%
See 1 more Smart Citation
“…In that report, the tumor showed high FDG uptake. 11 Our patient's IPT-like FDCT also showed high FDG uptake, but 18 F-FDG-PET or PET/CT may not be helpful for the differentiation of IPT-like FDCT from other splenic tumors because some splenic tumors, such as metastatic tumors or lymphomas, can also show high FDG uptake. 20 Further evaluation after the collection of many more cases is required regarding the FDG uptake of FDCTs and the utility of 18 F-FDG-PET or PET/CT for the differential diagnosis of FDCTs from other splenic lesions.…”
Section: Only 19 Cases Of Splenic Ipt-like Fdcts or Iptsmentioning
confidence: 57%
“…4 with EBV positivity have been reported. 2,4,[6][7][8][9][10][11][12] Ten of 19 cases have been described their imaging findings (Table 2). [6][7][8][9][10][11][12] Of them, CT findings were described in 8 cases, all of which showed a well circumscribed margin.…”
Section: Discussionmentioning
confidence: 99%
“…The patient did not receive chemotherapy after the rst hepatectomy. Tsunemine et al 18 suggested that TACE was useful for the management of hepatic FDC sarcoma, and the patient was still alive more than 2 years after the diagnosis with hepatic tumors favorably controlled by repeated TACE. Shinagare et al [20] reported a case which the patient was not determined to be a surgical candidate because of large tumor mass and small residual liver volume.…”
Section: Discussionmentioning
confidence: 99%
“…FDCS of the liver is a very rare entity, first reported in 1996 by Shek et al (4) and with only 17 reported cases in the English literature to date (1,4,(5)(6)(7)(8)(9)(10)(11)(12). Clinical, pathological and surgical features of these cases with complete histological and IHC details were reviewed and summarized ( Table 1).…”
Section: Discussionmentioning
confidence: 99%